Relevance Of Legal Certainty In Criminal Of Consent In The Eradication Of Corruption Law - Haryono Haryono; Bambang Tri Bawono (Law Development Journal, 2021)
This study aims to analyze and determine the construction of evil consensus in corruption in Indonesia; legal weaknesses in cases of criminal conspiracy in corrupt criminal acts as well as reconstruction of evil conspiracy in criminal acts of corruption based on progressive law. The research uses a sociological juridical approach. Based on the research conducted, it was found the fact that the implementation of law enforcement in cases of conspiracy related to corruption is currently not fair, this is due to the unclear elements in the criminal act of conspiracy in corruption cases so that existing law enforcement is based on political interests, where the authorities will be able to looking for a way out of the snares of Article 15 of Act No. 31 of 1999 Jo. Act No. 20 of 2001 concerning the Eradication of Criminal Acts of Corruption, while parties who do not have the authority to power will not be able to escape the snares of Article 15 of Act No. 31 of 1999 Jo. Act No. 20 of 2001 concerning the Eradication of Corruption Crimes.